2010
DOI: 10.1007/s10096-010-0891-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of bacteria in ascites—reporting the potential of culture-independent, molecular analysis

Abstract: Spontaneous bacterial peritonitis (SBP) is a severe complication of liver disease. A significant proportion of patients have culture-negative ascites, despite having similar signs, symptoms and mortality to those with SBP. Therefore, empirical antibiotic treatment for infection is often started without knowledge of the causative organisms. Here, we investigated the potential of molecular techniques to provide rapid and accurate characterisation of the bacteria present in ascitic fluid. Ascites samples were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…However, recent studies using 16S rRNA-based fingerprinting analyses have shown that ascites may also be polymicrobial (10,11) and that the bacterial spectrum is broader than that previously reported in context with SBP (11).…”
mentioning
confidence: 71%
“…However, recent studies using 16S rRNA-based fingerprinting analyses have shown that ascites may also be polymicrobial (10,11) and that the bacterial spectrum is broader than that previously reported in context with SBP (11).…”
mentioning
confidence: 71%
“…Following incubation, pellets were exposed to light for 10 min using an LED Active Blue equipment light source (Ingenia Biosystems, Terrassa, Spain). Total DNA extraction was then performed as described previously [13]. Full details of the protocol used are provided as Methods S1.…”
Section: Methodsmentioning
confidence: 99%
“…This assay was described previously [24], and applied in the analysis of ascites [13]. Full details of the protocol used are provided as Methods S1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular methods based on species-specific PCR or broad- range PCR for detecting the 16S rRNA gene followed by sequencing for species identification are being increasingly used for the etiological diagnosis of purulent infections, including SBP, septic arthritis, or CAPD-related peritonitis (4,7,8,12,18,19). These assays have been shown to improve the diagnostic efficiency of culture methods due to their higher sensitivities, especially with samples obtained from patients who have been exposed to antibiotics prior to specimen sampling.…”
mentioning
confidence: 99%